Analisis Manajemen Logistik Penyimpanan Obat di Instalansi Rumah Sakit X : Literatur Review - Diana Safitri; Hendra Deswita; Renal Renal; Budi Hartono (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Hospitals, as healthcare service institutions, play a crucial role in providing high-quality and effective healthcare services. One critical aspect in achieving this goal is effective logistics management for drug storage. This literature review aims to analyze the logistics management of drug storage at the pharmacy unit of Hospital X. The literature search yielded 10 relevant articles on the analysis of drug storage logistics management in hospital pharmacy units. The databases used included Google Scholar, Science Direct, and Semantic Scholar. The keywords applied were logistics management, drug storage, and hospital. The search results underwent a filtering process using PICO elements and the CRAAP method. The findings indicate that logistics management strategies in pharmacy units demonstrate success in several aspects, such as procurement and administration. However, significant challenges lie in human resource limitations, the effectiveness of planning methods, and the availability and security of storage spaces. Integrating information systems, enhancing human resource training, and adopting data-driven management are the primary recommendations for improving pharmaceutical logistics efficiency in the future.